Analisis Hidrologi Embung Kali Belik UGM dengan HEC-HMS - ACHMAD, Achmad ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the watersheed management objectives is to optimize hydrology condition. Water system condition can be identified from the nature streams as a watersheed output. Flood occurance in watersheed is one of the example why watersheed management required. In this case flood located in Belik river UGM. Reservoir is one way of watersheed management to solve flood problem. Hydrology analysis needs to be done in order to determine the capability of reservoir to solve flood problems. HEC-HMS software used in this study is one of the way to run hydrologic simulation. In HEC-HMS, Initial and constant method chosen to calculate the effective rainfall (loss method). Synthetic Hydrograf of Nakyasu method used to simulate Transformation of effective rainfall into flow hydrograph (direct runoff). Hydrograph flow HEC-HMS is the total of the direct flow coupled with the base flow (baseflow) derived by the method of the recession. Flood discharge out of the designed reservoir was calculate by performing a flood routing on the HEC-HMS software, by adding spillway components in basin models. The result shows that using design rainfall 5 years period of 120 mm, the design flood discharge is 8,784 m3/s. flood routing of HEC-HMS give result that flood discharges comes out of the designed reservoir is 8,318 m3/s for the reservoir without the outlet orifice and 8,165 m3/s for the reservoir with outlet orifice. Capacity of the river was 4,5 m3/s so that a reservoir is not enough to solve the problem of flooding in Belik river.